คาริโอไทป์ของพืชสกุลหอมกระเทียม 6 ชนิดในประเทศไทย: Karyotypes of Six Species in Allium (Alliaceae) in Thailand - Donsakul, Thawat; Phornphisutthimas, Somkiat (Asian Health, Science and Technology Reports, 2010)
This research aimed at investigating the karyotypes of onion and garlic in Thailand: Allium ascalonicum L., A. cepa L. var. aggregatum G. Don, A. cepa var. viviparum (Metzg) Alef., A. fistulosum L., A. ampeloprasum L., A. sativum L. (large cloves), A. sativum L. (small cloves), and A. tuberosum Roxb. To analyse the karyotypes, chromosomes were prepared from root tips and stained with Giemsa’s stain. The results indicated that A. ascalonicum, A. cepa var. aggregatum, A. cepa var. viviparum, A. fistulosum, A. ampeloprasum, A. sativum (large cloves), and A. sativum (small cloves) had the same chromosome number of 2n = 2x = 16 while A. tuberosum had the chromosome number of 2n = 4x = 32. The karyotypes of A. ascalonicum and A. cepa var. aggregatum comprised 6 metacentric (m) + 1 submetacentric (sm) + 1 subtelocentric (st) pairs with the arm number (NF) of 30. The karyotpes were 5m + 2sm + 1st pairs in A. cepa var. viviparum with NF = 30, 6m + 1sm + 1st pairs in A. fistulosum with NF = 30, and 6m + 2sm + 2t pairs in A. ampeloprasum, A. sativum (large cloves), and A. sativum (small cloves) with NF =32. However, A. tuberosum had the chromosome number of 2n = 4x = 32, as well as its karyotypes composed of 12m + 2sm + 2t pairs with NF =60. The average of chromosomal size was in a range of 3.890 and 6.059 μm. Clearly distinguished by chromosome characteristics, Allium can be divided into two groups: (1) onion group had satellited chromosomes, and (2) garlic group had secondary constrictions on their chromosomes.